BER Analysis of Reconfigurable of Non-Orthogonal Multiple Access (NOMA) for 5G Technology - Priyanka Markam, Munna Lal Jatav (International Journal of Research & Technology, 2021)
Exploring NOMA for regular downlink and uplink frameworks, the utilization of NOMA is examined in downlink multiuser numerous information different yield (MIMO) frameworks, by proposing a novel MIMO-NOMA model with direct beamforming method. In this MIMO-NOMA framework, clients' get receiving wires are progressively assembled into various disjoint bunches, and inside each group a solitary bar is shared by all the get reception apparatuses those embrace NOMA. The prevalence of the proposed model is represented through broad execution assessments. At long last, the utilization of facilitated multi-point (CoMP) transmission procedure is examined in downlink multi-cell NOMA frameworks, considering disseminated control assignment at every phone. In the proposed CoMP-NOMA model, CoMP transmission is utilized for clients encountering solid get signals from different cells while every phone autonomously receives NOMA for asset designation. The relevance and vital conditions to utilize diverse CoMP plans are recognized under different system situations, and the relating throughput equations are determined. The ghastly proficiency increases of the proposed CoMP-NOMA model are additionally evaluated.